PERSEPSI PENDIDIK MADRASAH IBTIDAIYAH SUMATERA BARAT TENTANG KOMPETENSI YANG DIMILIKINYA - Meria, Aziza (JMIE (Journal of Madrasah Ibtidaiyah Education), 2017)
This study aims to explore and get a picture of the perception of educators Maadrasah Ibtidaiyah about the competence it has. Along with the birth of Law Number 20 Year 2003 on National Education System and Law Number 14 Year 2005 on Teachers and Lecturers, the teachers have been recognized as professions. As a profession, teachers must have clear and measurable competencies. Teacher competence is four, namely: pedagogic competence, professional competence, social competence, and personal competence. Efforts to improve competence can be done if the educator has a good perception of the competence he has. Please note how the perception of MI educator to pedagogic, personality, social, professional and religious competence, so that later can be known what actions or programs that can be done in improving their competence.